The role of company reputation in mitigating negative word of mouth - Rahmani, Shinta; Halim, Rizal E.; Gayatri, Gita; Furinto, Asnan (Business: Theory and Practice, 2021)
The study aims to investigate whether a company reputation can be used to reduce the impact of negative electronic word of mouth (eWOM). We conducted experimental research in two studies along with 225 college students, who at least have two accounts in different social media, as participants. We use both qualitative and quantitative methodologies. Qualitative research was carried out with focus group interviews to decide the number of high or low negative reviews as well as the level of credibility. Quantitative research used cross-sectional field design by pilot study and the main study. The model was tested and developed using data collected by questionnaires in paper surveys. The results of study 1 suggest that negative eWOM reduces purchase intentions mediated by the subjective norms and perceived behavior control. High negative eWOM reduces purchase intention more than low ones. Study 2 found out that in a condition of high negative eWOM, good company reputation’s perception affected purchase intention mediated by attitude. Furthermore, purchase intention is higher when a good company reputation’s perception is stronger. Therefor Organizations should convey its company reputation to their customer visually to get a good perception. Further research to investigate another variable that the company has is required.